Mictomagnetic full-Heusler nanoprecipitates in (Ti, Zr, Hf)NiFexSn half-Heusler composites. (December 2019) - Bailey, T.P.; Lu, R.; Poudeu, P.F.P.; Uher, C.
Abstract: One of the most recent strategies used to enhance the efficiency of certain thermoelectric (TE) materials relies on the interaction of magnetic dopants with charge carriers and lattice vibrations. Understanding the forms of magnetism inherent to the materials is critical for continued TE performance optimization. Accordingly, we herein analyze the low-temperature magnetic properties of a mictomagnetic composite system we previously engineered for improved TE power generation capabilities. The Ti0.25 Zr0.25 Hf0.50 NiFe x Sn0.975 Sb0.025 set of materials features long-range magnetic ordering as a result of an intentional magnetic full-Heusler secondary phase in the half-Heusler composites. Having the highest population density of magnetic nanoprecipitates, the x = 0.05 sample exhibits both superparamagnetic and cluster glass behavior, with blocking temperatures ranging from ≈ 100 to 250 K. We discern the phenomena from the sharp, open DC magnetization loops, the splitting of the zero-field-cooled and field-cooled DC moments, as well as the frequency- and field-dependent AC susceptibility measurement. In the magnetotransport data, we find evidence for the Kondo effect in these dilute magnetic semiconductors, in addition to weak antilocalization in the pure sample that is abated in the magnetic samples. Graphical abstract: Image 1 Highlights: Range of magnetic full-Heusler nanoprecipitate sizes leads to mictomagnetism. AC susceptibility is used to investigate glassy magnetic phenomena for x = 0.05. Both superparamagnetism and cluster glass behavior present, Tf ≈ 175 K. Kondo effect manifested as resistivity minima near 25 K in magnetic samples. Weak antilocalization in the Fe-free sample is suppressed in magnetic samples.